Perkembangan Sejarah Kebudayaan Islam di Kerinci - Roni, Muhamad Aldian; Sinurat, Junita Yosephine (Lambung Mangkurat University, 2024)
This research was carried out with the aim of finding out more deeply about the historical development of Islamic culture in Kerinci. People in Kerinci still don't know much about the historical and cultural heritage of Islam in Kerinci. This type of research uses qualitative descriptive techniques. Research findings show that the construction of mosques is a fundamental aspect of Islamic society. However, the process of building a mosque involves a combination of Islamic, indigenous and foreign cultural elements. Based on the mosque's use at that time, apart from being a place of worship, this mosque also functioned as a place for religious discussions.